Failure pressure estimation of corroded pipeline with different depths of interacting defects subjected to internal pressure - Ahmad Azmy, A. (2013)
Pipelines are one of the most reliable and safest ways to transport oil and gas from one location to another. However, if not handled and maintained properly, they will cause major destruction should one of these pipelines burst. A pipeline which has oil or gas flowing through it will be subjected to internal pressure due to the flow of the oil or gas. Furthermore, the chemical composition of the oil and gas acts as a corrosive agent towards the pipeline. The corrosion eventually becomes defects thus compromising the pipeline integrity. In addition, if two defects are close enough, they are treated as interacting defects. In this work, the pipeline integrity was first calculated using DNV RP-101 codes. After calculating the maximum operating pressure for the pipeline using the codes, Finite Element Analyses using ANSYS were carried out to simulate and model the pipeline with the interacting defects. The maximum operating pressure given by the FEA was then compared to the DNV codes. We found that despite consistency between DNV codes, the FEA analysis showed that geometry plays an important part in determining the values of failure pressure. The FEA analysis showed that by increasing the ratio of depth between the interacting defects, the failure pressure decreases. This was likely because defects of larger depths are more likely to fail at lower pressures. This contradicts the results obtained from DNV codes where the failure pressure is constant for the same effective defect depth over thickness, (d12/t)*. Â© (2013) Trans Tech Publications, Switzerland.